{One-electron reduction of 8-bromo-2-aminoadenosine in the aqueous phase: Radiation chemical and DFT studies of the mechanism} - Kaloudis, P; D'Angelantonio, M; Guerra, M; Gimisis, T.; Mulazzani, Q G; Chatgilialoglu, C (J. Phys. Chem. B, 2008)
Two tautomeric forms of one-electron oxidized 2-aminoadenosine (2AA) have been produced by reactions of hydrated electrons (e(aq)(-)) with 8-bromo-2-aminoadenosine (8-Br-2AA) at natural pH, whereas only one tautomer is formed by oxidation of 2AA. Tailored experiments by pulse radiolysis and time-dependent DFT (TD-B3LYP/6-311G**//B1B95/6-31+G**) calculations allowed the definition of the reaction mechanism in some detail. The electron adducts of 8-Br-2AA protonated at C8 eject Br- and produce the two short-lived tautomers (8 and 9). The first observable species decays by first-order kinetics to produce the second intermediate, which is also obtained by oxidation of 2AA by SO4 center dot-. The rate of tautomerization (k(taut) = 4.5 x 10(4) s(-1)) is strongly accelerated by phosphate and is retarded in D2O (kinetic isotope effect 7). B1B95/631+G** calculations showed that the tautomerization is a water-assisted process. In acidic or basic solutions, the "instantaneous" formation of one-electron oxidized 2AA or its deprotonated forms has been produced by reactions of e(aq)(-) with 8-Br-2AA. gamma-Radiolysis of 8-Br-2AA in aqueous solutions followed by product studies led to the formation of 2AA as a single product.